Reading and text comprehension - Milito, Francesco (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2019)
Media has the responsibility to convey people’s habits towards forms of homologation, even managing to affect the period of attention, on language skills, lexical and written expression. Is the debate of exploring issues related to reading still useful? Words appear threatened in its written form, it risks losing the essence that characterizes it, affecting itself negatively especially the quality of the message that is being transmitted, even orally. The social structures characterized by the rapid cultural evolution require that young people interpret texts in order to find useful information to the structuring of thought and are able to contribute to the development of one’s own intellectual capacity. The school’s task is to pursue the goal of development of critical mentalities, to favor student’s choices related to the information that may be considered or refused. The teacher’s task is to identify contents, time and useful methods.